Vocal individuality of Sunda Scops Owl (Otus lempiji Horsfield, 1821), Brown Boobook (Ninox scutulata Raffles, 1822) and Spotted Wood Owl (Strix seloputo Horsfield, 1871) in Peninsular Malaysia - Yee, Siew Ann (2016)
Sunda Scops Owl (Otus lempiji Horsfield, 1821), Brown Boobook (Ninox scutulata Raffles, 1822) and Spotted Wood Owl (Strix seloputo Horsfield, 1871)are commonly found in semi-open as well as forested habitats in Peninsular Malaysia yet they remain understudied. Nocturnal habit, secretive nature and cryptic coloration of these birds cause difficulties in their monitoring using traditional survey techniques. Individual variations in vocalisation can potentially be used to distinguish different individuals of an owl species as being demonstrated for many bird species. The objectives of this study were (1) to describe the territorial call of these three owls; (2) to determine whether their calls can be distinguished individually; (3) to examine whether the calls from the same individuals were stable over time; and (4) to examine whether there were differences in the calls of the same species between two habitat types. In total,75 recordings from 12 Sunda Scops Owls, 16 recordings from four Brown Boobooks, and 14 recordings from three Spotted Wood Owls were collected from June 2014 to June 2015 in a lowland forest and the oil palm smallholdings in Selangor, Peninsular Malaysia. From spectrograms produced using Raven Pro 1.5, two temporal parameters were measured for all the three owl species.Five frequency parameters were measured for the Sunda Scops Owl whereas it was six for Brown Boobook, and only three for Spotted Wood Owl. Kruskal-Wallis tests found significant individual differences (P < 0.001) in each parameter measured for each species. Discriminant function analysis (DFA)achieved 96.8% classification success for the Sunda Scops Owl, and it was 100% for the other two owl species. Based on Wilcoxon signed ranks tests, most of the measured vocal parameters from the Sunda Scops Owls did not vary significantly (P > 0.05) between two pre-determined survey periods. The sample size of the other two owl species was too small to allow temporal comparison.Based on scatterplot derived from DFA, intraspecific difference with respect to two different habitats was found for the Sunda Scops Owl. Overall, this study suggested that the territorial calls of the three Malaysian owl species differed individually and this will aid in the survey and monitoring of these birds at night based on their vocalisations. Such method can be further tested for other little known owl species in the tropics.